Perencanaan Tata Ruang Bagian Wilayah Perkotaan Kepanjen, Studi tentang Konsistensi Pelaksanaan Rencana Detail Tata Ruang Bagian Wilayah Perkotaan Kepanjen Tahun 2014-2034 - Trivinata, Rina (Jurnal Ilmiah Administrasi Publik, 2016)
This paper examines spatial planning and consistency between planning and field condition facts. The author collected the data from Observations, interviews, and documentation. Results: Findings showed that spatial planning at Kepanjen Urban Areas is relevant to the ninth principles of spatial planning in accordance with the Law on Spatial Planning and also control results (licensing) and the nine aspects of the control system to see the consistency of the implementation of Kepanjen Urban Area 2014-2034. The results indicate that spatial planning of Kepanjen Urban Area is relevant with the nine principles of spatial planning but there has been no form of partnership in planning. There is consistency in the implementation of Kepanjen Urban Area 2014-2034 in 12 suburbs/villages.